1988
DOI: 10.3109/10641968809033899
|View full text |Cite
|
Sign up to set email alerts
|

Low TRH-TSH Responses in Human Essential Hypertension

Abstract: Thirty female and male essential hypertensive patients and eighteen normotensive controls were submitted to the TRH-TSH conventional test (200 ug intravenously, bolus injection of TRH). Supramaximal doses of 400 and 600 ug were repeated with a week interval to each subject. Hypertensives showed a significant lower response to both conventional and supramaximal TRH doses. Hypothalamic-pituitary-thyroid axis abnormalities, secondary to TRH-receptor alterations, could account for this result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…6,7 It was thus tempting to speculate that the component genes of the TRH system may be associated with essential hypertension. Because Lupi et al 9 reported that hypertensive patients have a blunted TSH response to TRH, indicating that there is a possible defect in the TRHR activation-mediated TSH release, we postulated that TRHR may be also involved in essential hypertension. Accordingly, we searched for molecular variants of the TRHR gene promoter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 It was thus tempting to speculate that the component genes of the TRH system may be associated with essential hypertension. Because Lupi et al 9 reported that hypertensive patients have a blunted TSH response to TRH, indicating that there is a possible defect in the TRHR activation-mediated TSH release, we postulated that TRHR may be also involved in essential hypertension. Accordingly, we searched for molecular variants of the TRHR gene promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Many endocrine disorders arise from mutations of these receptors, which result in changes of their basal or ligand-induced activity. 8 In this regard, Lupi et al 9 have demonstrated that hypertensive patients have a blunted TSH response to intravenous TRH bolus injection, suggesting a defect in the TRHR activationmediated TSH release. In summary, we postulated that the TRHR gene is involved in human hypertension.…”
mentioning
confidence: 99%
“…As seen in several neuroendocrine diseases, mutations of these receptors may result in constitutive activation. Since it has been demonstrated that hypertensive patients have a blunted TSH response to TRH injection suggesting a defect in the hTRH-R [55], we postulated that the hTRH-R gene is involved in essential hypertension. We studied two independent populations from different geographic regions of our country, a sample of adult subjects from a referral clinic and a population-based sample of high school students.…”
Section: Extrahypothalamic Trh In Human Hypertensionmentioning
confidence: 97%